A comparison of the efficacy and safety of a half dose of fluticasone propionate with beclamethasone dipropionate and budesonide in childhood asthma - KARADAĞ, BÜLENT TANER; SAVE, DİLŞAD (My University, 2001)
This study was carried out in an attempt to compare the efficacy and safety of fluticasone propionate (FP) at the half dose of budesonide (BUD) and beclamethasone dipropionate (BD) in childhood asthma. Ninety-six children with moderate to severe asthma (9.6 +/- 2.17 years) whose asthma was already controlled on BUD (n = 52) or BD (n = 44) were recruited into the study. In the first part of the study (the first 12 weeks) each group was followed with three weekly lung function measurements, daily diary records, and peak expiratory flow (PEF) measurements on the initial medication. At the end of 6 weeks, drugs were switched to a half dose of FP, and the subjects were followed for another 6 weeks. Blood samples were obtained for osteocalcin and plasma cortisol levels after each treatment period. In the second part of the study, 50 patients continued to take FP at the half dose of BUD or BD for another 30 weeks. Clinic visits, including lung function and PEF measurements, were conducted every 10 weeks. After 6 weeks of FP treatment, there was a small but statistically significant decrease in FEV1 and FEF(25-75) in both groups (BUD and BD) without any significant obstruction. These mild changes in lung function measurements continued during long-term follow-up. However, there was no statistically significant further decrease in any lung function parameters while receiving FP (visits 3-8) (coefficient = -0.00751 L/day, p = 0.39 for FEF(25-75) and coefficient = -0.00910 L/sec/day, p = 0.055 for FEV1). There were no significant changes in the morning and evening PEF measurements and diurnal PEF variations after 6 weeks of treatment with FP compared with BUD and BD treatments. There were no significant changes in basal cortisol and osteocalcin levels before or after 6 weeks of FP treatment (p > 0.05). The present study concluded that, although FP at the half dose of BUD or BD seems to maintain reasonable control of the disease symptoms, a mild but significant and persistent decrease in lung function parameters may indicate that FP may not be twice as potent as BUD or BD in childhood asthma by evaluation of lung functions. This conclusion must be further verified with long-term studies.
Keywords: Female; Humans; Male; Follow-Up Studies; Child; Time Factors; Anti-Inflammatory Agents; Administration, Inhalation; Asthma; Budesonide; Androstadienes; Anti-Asthmatic Agents; Beclomethasone; Fluticasone; Respiratory Function Tests